2018
DOI: 10.32894/kujss.2018.13.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ruminants Gastro-Intestinal Parasites in Kirkuk province, Iraq

Abstract: The present study was established on the slaughtered ruminants in Kirkuk central abattoir between June 1 st till December, 31 st 2015. The aim of the study is to determine the prevalence of gastro-intestinal parasites (GIP s) of slaughtered grazing ruminants in Kirkuk province. Fresh faecal specimens (n=276) were obtained from slaughtered grazing ruminants (85 sheep, 71 goats and 120 Cattle) in Kirkuk province. The investigational processing represented as direct and concentration methods were carried out usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
1
4
2
Order By: Relevance
“…In the present study, the overall prevalence of nematodes parasite was(42%) these finding disagree with [23] in Baghdad(51.94%) and with [24] in Mosul (62.9%) Ten genus of Nematodes were identified in this study ,these result disagree with [25] in the Kirkuk city ,were detected four genus of Nematodes in sheep.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the overall prevalence of nematodes parasite was(42%) these finding disagree with [23] in Baghdad(51.94%) and with [24] in Mosul (62.9%) Ten genus of Nematodes were identified in this study ,these result disagree with [25] in the Kirkuk city ,were detected four genus of Nematodes in sheep.…”
Section: Discussioncontrasting
confidence: 99%
“…The high percentage of gastrointestinal parasites infection in different regions of Basrah province infection without significant difference may be attributed to open grazing in pasture. Through laboratory examination of 255 fecal samples by using direct examination and concentration methods to diagnosis S.papillosus we could detect (7.54 %) while serological examination detect(34.7%) that agrees with [23] reported (35.29%) in Diyala, (9) (11.49%) in mosul province, [8] were (10.7%) in Kirkuk provinc and [24] reported (28.45%) in India while disagree with (10) reported (2.8%) in Basrah province, (24) were observed (3.4% ) in India and (25) were observed (0.49%) in India.…”
Section: Discussionsupporting
confidence: 88%
“…The present study demonstrated the percentage of the gastrointestinal parasites species depend on sex (Table 7). The percentage of sensitivity and Specifity in ELISA(SS-IgM) kit which estimated as in table (8). Sensitivity % = =100% Specifity % = = 88.8%…”
Section: Identification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…is considered to be one of the most common GIN reported in small ruminants (Kaplan et al, 2004;Hassum, 2014;Sivajothi and Reddy, 2018). There are several reports available, in which the prevalence of GIN parasites varied from 50.51-86.05% from different parts of India (Pathak and Pal 2008;Tariq et al, 2010;Choubisa and Jaroli 2013;Gul and Tak, 2016;Dappawar et al, 2018;Verma et al 2018) and similarly from other parts of the world (Ntonifor et al, 2013), Slovakia (95.9%) (Babjak et al, 2017), West Indies (98%) (Chikweto et al, 2018) and Iraq (91.5%) (Hassan and Barzinji 2018). The variation in occurrence of different percent prevalence of GIN parasites might be due to different agro-climatic situations prevailing in the different region and zones.…”
Section: Resultsmentioning
confidence: 99%